Tujuan Instruksional Khusus dalam Desain Instruksional Modern dalam Analisis Proses Pembuatan TP dan ATP di Kelas 1 SDN 15 Tangerang - Magdalena, Ina; Fitri, Indah Zianira; Mulyaningsih, Yuni (YASIN, 2023)
This research is expected to reveal the uniqueness of the educational goals that are structured in SDN 15 TANGERANG. The strategy to be used during the exam is riveting technique through subjective methodology. The item to be contemplated is a class 1 teacher at SDN 15 TANGERANG. The interactions that will be used this time are interview and documentation strategies. The breakdown of explicit learning objectives includes only students and behaviors. The presentation technique is that most of the teachers apply a speaking strategy using powerpoint slide media which occurs when web-based learning begins and online question and answer then assignments are given online and assignments are collected. The implementation of special education is recognized by having a facilitator responsible for equipment and supplies, for example the main daily schedule called the homeroom teacher, which has configuration factors, namely: 1) Mastery of web-based learning planning; 2) Acknowledgment of educator preparation; 3) Skills in applying ideas to new situations in various ways; 4) make the school a learning association; 5) Schools can supervise in organizing, coordinating, planning and managing; 6) the capacity to overcome problems with a methodical movement towards learning; 7) Ability to describe and assess mastery results.